Barisan Modul Eksak dan Barisan Homomorfisma Modul Eksak - Yanita Yanita (Matematika, 2008)
This article explained  sequence exact of R-module and R-module homomorphism and their  relation.  Module is generalized of vector space V over field F.  If  M module over ring R, usually  denoted M R-module.  Module sequence is defined as homomorphism sequence from module to another module.  R-Module sequence have exact property at a module, for example Mi, if  kernel function from Mi to Mi+1 same with  image function from Mi-1 to Mi.  The set of all R-module homomorphisms from Mi to Mi+1 will be denoted HomR(Mi,Mi+1).  HomR(Mi,Mi+1) is also module over ring which the same with  Mi and Mi+1.